Evaluation of Effects of Systemic Zoledronic Acid Application on Bone Maturation in the Consolidation Period in Distraction Osteogenesis - Akbulut, Yasin; Gul, Mehmet; Dundar, Serkan; Ozcan, Erhan Cahit; Ozercan, Ibrahim Hanifi; Bozoglan, Alihan; Bingul, Muhammet Bahattin (Lippincott Williams & Wilkins, 2021)
Distraction osteogenesis (DO) is a physiological process that generates new bone tissue formation, using progressively separated bone fragments. Recently, several techniques have been investigated to develop the maturation of the new bone tissue. Bisphosphonates was an effective material for the acceleration of bone formation in DO procedures. The purpose of this study was to evaluate the effects of the systemic zoledronic acid application at the beginning of the consolidation period on new bone genesis in a DO model of rat femurs. The rats were divided randomly into 3 groups, as follows: Control group (CNT group) (n = 10), zoledronic acid dosage-1 (n = 10), and dosage-2 (n = 10) groups (ZA-D-1 and ZA-D-2). No treatment was administered in controls, but DO was applied to the rat femurs. A single dose of 0.1 mg/kg and 0.2 mg/kg of zoledronic acid was administered systematically at the beginning of the consolidation period after the distraction in treatment groups, respectively. Histomorphometric analyses were performed on the original distracted bone area and the surrounding bone tissue. Osteoblasts, new bone formation, and fibrosis were scored. New bone formation in the ZA-D-1 and ZA-D-2 groups, when compared with the control group, was detected highly (P < 0.05). The numbers of osteoblasts in the ZA-D-1 and ZA-D-2 groups were higher when compared with the controls (P < 0.05). Fibrosis in the controls, when compared with the ZA-D-1 and ZA-D-2 groups, was found to be higher (P < 0.05). Zoledronic acid application is an effective method for bone maturation in consolidation period in DO.
Keywords: Bisphosphonate; bone; distraction osteogenesis; femur; zoledronic acid